Amemboa Esaki (Hemiptera: Gerromorpha: Gerridae) of India, with descriptions of two new species and establishment of species groups of world species - Jehamalar, E. Eyarin; Dash, Swetapadma; Chandra, Kailash; Raghunathan, Chelladurai (Zootaxa, 2023)
Two new species of Gerridae, Amemboa latoae Jehamalar & Dash, new species and A. zetteli Jehamalar & Dash, new species, are described from India. Amemboa latoae is described from Meghalaya and can be recognised by the presence of the two setal tufts on the flexor region of the male fore femur and the slightly dilated midlateral region of the main part of the proctiger. Amemboa zetteli Jehamalar & Dash, new species, is described from Andaman Island and can be identified by the presence of the three setal tufts on the flexor region of the male fore femur; the rhombus-shaped main part of the proctiger of the male and the shape of the posterior region of the pygophore. Eleven species groups of Amemboa are also recognized in the present paper.